The Use of Request Strategy in Leave the World Behind Movie - Khairunisa, Naila Putri; Aprilia, Intan Ika; Rosalinah, Yanti (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The title of this study is "The Use of Request Strategy in the Movie Leave The World Behind by Sam Esmail." The purpose of this study is to analyze how characters in the movie make requests or ask someone to do something. The analysis is based on Trosborg's request theory using a descriptive qualitative approach. This study collected 18 data from dialogues in the movie. The analysis found that there are six request strategies used by the characters. The most frequently used strategy is the hint strategy, which allows characters to express their desires implicitly, avoiding the impression of being forceful or offending the listener. Besides the hint strategy, other identified strategies include questioning the hearer’s ability or willingness, statements of the speaker’s wishes and desires, statements of the speaker’s need and demands, statements of obligations and necessities, as well as the use of imperatives. The findings show that the variation in request strategies reflects the social dynamics and relationships among the characters, influenced by the specific context and communication objectives within the movie.